Studi Literatur: Penggunaan Software Geogebra terhadap Kemampuan Pemahaman Matematis Siswa - Siregar, Tiur Malasari; Syakira, Risya Indah; Saragih, Rini Meilani; Siregar, Rizki Aulia Rahma; Simangunsong, Ingrid; Purba, Miranda Br (Jurnal Akademik Pendidikan Matematika, 2024)
This research is important to explore the potential of GeoGebra as an innovative learning tool in mathematics education. Amid rapid technological advancements, GeoGebra is expected to serve as an effective solution to help students understand complex mathematical concepts. By utilizing a literature review approach, this study collects data from various relevant sources regarding the application of GeoGebra in mathematics education. Based on the reviewed studies, the use of GeoGebra significantly contributes to improving students' ability to understand abstract concepts, especially in geometry. However, challenges exist in its implementation, such as limited technological infrastructure in schools and insufficient teacher training. With improved access to technology and teacher training, GeoGebra can be optimized as an effective tool for teaching mathematics.